Improvement in photo-device properties of CuO thin films for opto-electronic applications: effects of (Ni, Co) co-doping. (1st December 2022) - Gnanasekar, T; Valanarasu, S; Ade, Ramesh; Vimala Juliet, A; Ganesh, V; AlAbdulaal, T H; Bitla, Yugandhar
Abstract: We report co-doping effects of transition metal elements (Ni, Co) primarily on the opto-electronic properties of CuO thin films. CuO, CuO:Ni(1%), CuO:Co(1%) and CuO:Ni(1%):Co(1%) thin films were deposited via the spray pyrolysis route. Structural studies revealed the monoclinic CuO structure for all films. For all the films scanning electron microscope (SEM) images showed a crack-free and homogeneous surface. Photoluminescence (PL) spectra of all the films exhibited four emission peaks at 415, 451, 477, and 521 nm wavelengths. The optical bandgap ( E g ) values were around 2.12 eV, 2.18 eV, 2.05 eV and 1.84 eV for CuO, CuO:Ni(1%), CuO:Co(1%) and CuO:Ni(1%):Co(1%)thin films, respectively. CuO:Ni(1%):Co(1%) photo-device displayed a large responsivity ( R ) of 0.43 AW −1, external quantum efficiency (EQE) of 100% and detectivity ( D * ) of 9.55 × 10 9 Jones. Hence, co-doping of transition metal elements would be one of the effective approaches for enhancing opto-electronic properties of metal oxide compounds.